Determination of Critical Indicators for Community-Based TPS 3R Performance - Siti Ainun Saleh; Mohamad Rangga Sururi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The Ministry of Public Works and Public Housing (Kementerian Pekerjaan Umum & Perumahan Rakyat – PUPR) has developed a guideline for assessing the performance of Waste Processing Sites in terms of Reduce, Reuse, and Recycle (Tempat Pengelolaan Sampah Reuse, Reduce, dan Recycle - TPS 3R) across five waste management aspects: regulations, technical technology, management institutions, finance, and community participation. The guideline includes parameters and indicators, but their definitions are not clearly specified, leading to various interpretations. This study aimed to identify the key indicators for measuring the performance of TPS 3R. The study involved defining and determining sub-indicators for each aspect using the constructive alignment concept to ensure clarity in measurement. These sub-indicators were consolidated into a set of questions for use in field data collection. The developed guidelines were applied to evaluate TPS 3R performance in West Java, using a comparative study and descriptive analysis for the evaluation. The study identified the critical indicators for each aspect as follows: (i) waste segregation for community participation, (ii) complete waste processing (sorting, organic waste processing, and inorganic waste handling) for technical aspects, and (iii) active management (waste and financial records) for management institutional aspects. These critical indicators not only influence the financial aspect but also provide economic support for the sustainability of TPS 3R.